PENGARUH MODEL PEMBELAJARAN SIKLUS TERHADAP HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN EKONOMI DI SMA CENDANA PEKANBARU - Nildawati, Yulia; Gimin, Gimin; Nas, Syakdanur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :The background of this research by studying the results of theeconomic subjects achieved by the students of Senior High SchoolCendana Pekanbaru that generally not reached the minimum score criteria(KKM) that is 78. Learning economy in this school is still generallycentered on the teacher (teacher center) and only occasionally engage thelearners. During this time, teachers implemented conventional learning.On the other there are many models of learning that can lead to studentsactive and make learning more meaningful, one of them is model of 5Elearning cycle. The purpose of this study to determine students learningoutcomes using cycle learning model, the difference and how much theinfluence of this model toward learning outcomes.The population in this study were all students of class XI Social inSenior High School Cendana Pekanbaru that consist of 71 students thatincludes three classes. While the sample are a class XI Social 1 and XISocial 3 that consist of 46 students were previously given homogeneitytest. Data analysis techniques used are different test using the formulaindependent sample t-test and to determine how much the influenceof thismodel using the glass (Δ) formula.Posttest data shows the average value of the experimental classwas 85,13 while the average values of the control class is 79,83. Posttestresults was tested using different test with a significance of 0,0009 is lessthan 0,05 (set), it means there is a significant difference between theposttest results of experimental class and control class. The results ofdifferent test show there is an influence of learning cycle model towardstudent learning outcomes of class XI on economic subjects in SeniorHigh School Cendana Pekanbaru. Further, Glass (Δ) testing found themagnitude of the effect then explain the value of 0,8 included into broadcategories. Thus, it can be interpreted that the cycle learning model hasconsiderable influence toward student learning outcomes.Key Word : Model 5E Learning Cycle and Learning Outcomes